ANALYSIS OF IMPLEMENTATION OF ACCRUAL-BASED GOVERNMENT ACCOUNTING STANDARDS (CASE STUDY IN LABUHAN BATU DISTRICT BPKAD) - Siahaan, Septony Benyamin; Purba, Dimita H.P; Pasaribu, Dompak; Simanjuntak, Wesly Andri; Silitonga, Ivo Maelina; Nadapdap, Kristanty M. N; Rumapea, Melanthon (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze the implementation of accrual-based government accounting standards at BPKAD Labuhan Batu Regency and to analyze the suitability of the implementation of accrual-based government accounting standards in accordance with the Statement of Government Accounting Standards (PP No. 71 of 2010 and supported by PERMENDAGRI No. 64 of 2013). Methods of data collection using observation (observation), interviews, and documentation studies. The results on the regulatory and policy aspects show that Permendagri 64 of 2013 mandates local governments to provide regulatory and policy tools related to the implementation of accrual-based SAP, but still refers to PP 71 of 2010, while the use of Permendagri No. 64 of 2013 experienced problems related to adjusting cash-based accounting policies towards accruals to an accrual-based accounting system. The results on the budget aspect show that the obligation to implement accrual-based SAP requires BPKAD to adjust from a cash-based accounting system policy towards SIMDA 2.5 accruals to the SIMDA 2.7 accrual-based accounting system that is currently being implemented which is in accordance with PP No. 71 of 2010. The results of the information technology aspect show that the information technology used according to the BPKAD Secretary, namely the regional financial management application system uses SIMDA 2.7 which has been provided by the BPKP. The results on the human resource aspect show that the implementation of accrual-based SAP requires the Labuhan Batu District BPKAD to adjust from cash to accrual-based accounting system policies to the current accrual-based accounting system which is in accordance with PP No. 71 of 2010.Keywords: Accounting Standards Based on Governmental Accounting, Accrual Basis